2022
DOI: 10.1186/s12933-022-01479-8
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of the stress hyperglycemia ratio in patients with acute ST-segment elevation myocardial infarction: insights from a multi-center observational study

Abstract: Background Stress hyperglycemia is a strong predictor of adverse outcomes in patients with acute myocardial infarction (AMI). Recently, the stress hyperglycemia ratio (SHR) has been designed as an index to identify acute hyperglycemia with true risk; however, data regarding the impact of SHR on the prognosis of ST-segment elevation myocardial infarction (STEMI) remains limited. This study aimed to evaluate the predictive value of the SHR in patients with acute STEMI and to assess whether it can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 29 publications
1
37
0
Order By: Relevance
“…Sia et al found that SHR is an independent predictor of one-year mortality in patients with ST-segment elevation myocardial infarction (STEMI) with and without diabetes mellitus [ 27 ]. Xu et al reported that SHR was significantly associated with 30-day mortality in patients with STEMI and that the predictive efficiency of the TIMI risk score can be improved after adding SHR as one point [ 12 ]. Yang et al observed a J-shaped relationship between SHR and in-hospital cardiac death in patients with ACS who underwent the implantation of a drug-eluting stent [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sia et al found that SHR is an independent predictor of one-year mortality in patients with ST-segment elevation myocardial infarction (STEMI) with and without diabetes mellitus [ 27 ]. Xu et al reported that SHR was significantly associated with 30-day mortality in patients with STEMI and that the predictive efficiency of the TIMI risk score can be improved after adding SHR as one point [ 12 ]. Yang et al observed a J-shaped relationship between SHR and in-hospital cardiac death in patients with ACS who underwent the implantation of a drug-eluting stent [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The stress hyperglycemia ratio (SHR) represents relative hyperglycemia and has been proven to be effective in predicting worsening prognosis in patients with severe acute disease [ 9 ]. Several studies have reported that SHR was significantly associated with adverse clinical outcomes in patients with ACS [ 11 , 12 ]. However, this association may be a comprehensive effect of a heterogeneous population with ACS.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence outlines the strong and independent association of SIH with short- and long-term clinical outcomes in STEMI patients irrespective of the definition used for the diagnosis of SIH [ 3 , 5 , 25 , 26 ]. However, the exact mechanisms of this correlation are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…SIH is associated with increased short and long term major adverse cardiovascular events in patients with STEMI irrespective of the presence of diabetes [ 3 5 ]. However, the metabolic milieu in which SIH emerges during epicardial coronary artery thrombosis remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperglycemia is an important factor that determines endothelial dysfunction, leading to vascular damage and microvascular obstructions, and its effect of increasing oxidative stress, inflammation and platelet aggregation is also known. Thus, hyperglycemia causes a change in protein synthesis, with increased expression of pro-inflammatory factors (IL11, IL 6, TNF alpha, fibrinogen), oxidative stress and adhesion molecules (ICAM 1, VCAM 1), all of which result in endothelial damage and the appearance of atherosclerotic lesions [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%